Emerging drugs in refractory colorectal cancer. (August 2015) - Nobili, Stefania; Galletta, Alessandro; Brugia, Marco; Tassi, Renato; Petreni, Paolo; Landini, Ida; Mini, Enrico
Colorectal cancer is the third leading cause of cancer-related deaths in the western world. Despite therapeutic advances, the prognosis of metastatic colorectal cancer patients remains poor due to intrinsic or acquired tumor drug resistance. The main mechanisms of tumor drug resistance are represented by genetic and epigenetic alterations. This leads to tumor refractoriness during treatment or disease progression following response to first-line therapy. Strategies to combat chemorefractory tumors involve the development of selective inhibitors of drug-resistant phenotypes, the epigenetic resensitization of drug-resistant cancer cells and new cytotoxic drugs devoid of cross resistance with first-line cytotoxics. The use of drug combination regimens may also increase treatment efficacy, and the exploitation of specific phenomena such as oncogenic and nononcogenic addiction or synthetic lethality represents another potential approach in combating tumor drug resistance. Clinical trials based on such strategies in mCRC patients whose tumors progressed following first-line chemotherapy are discussed herein.